Petaflow - A project towards information and communication technologies in society - Gonçalves, P.; Grandchampy, X.; Pelorsony, X.; Raffinz, B.; Van Hirtumy, A.; Vicat-Blanc, P.; Baba, K.; Cisonni, Julien; Ebara, Y.; Nozaki, K.; Ohsaki, H.; Wada, S.; et al. (2010)
The Petaflow project aims to contribute to the use of high performance computational resources to the benefit of society. To this goal the emergence of adequate information and communication technologies with respect to high performance computing-networking-visualisation and their mutual awareness is required. The developed technology and algorithms will be applied to a real peta-scale data intensive scientific problem with social importance, i.e. human upper airway flow modelling. © 2010 IEEE.